Scenario planning and strategizing: an integrated approach - Wright, Alexis Duncan (2007)
This thesis presents an analysis of how one UK Regional Development Agency (RDA) used scenario planning in its construction of the region’s Regional Economic Strategy (RES). Strategists are broadly defined to include those within the RDA charged with developing and enacting a consultative strategy making process, the consultants engaged to provide advice and expertise to ensure workshops were conducted effectively, and, individuals representing stakeholder organizations that attended these workshops and responded to written consultations. Four scenarios depicting the region in the year 2020 were produced, which were subsequently presented as an evidence-base for the strategy process. A draft RES was created and issued for consultation. Previous RES development processes had been criticized for their lack of consultation, in this iteration strategists skilfully utilized a recognized strategy making practice as a means of responding to this. The scenario planning approach they adopted bore little resemblance to to the sanitised and context-free recipes commonly presented in the strategy textbooks. The research is a reflective, longitudinal study with data drawn from forty-six semi-structured interviews producing an authentic rich description that illustrates how actors enacted a strategizing process in the complex environment of the UK public sector. The analysis highlights how the strategists were influenced by sometimes conflicting desires and aspirations, and that to reconcile these and ensure deadlines were met inductive, interpretive and subjective acts were required. This analysis presents strategists as bricoleurs, with the documents and draft strategies produced being socially situated co-constructions emerging from negotiated, temporally-bound, power-laden and politically-infused interactions.